STUDI LITERATUR STRATEGI PEMBELAJARAN BERDASARKAN LITERASI MATEMATIKA - Lubis, Atipah; Simamora, Minta Ito; Yusnika, Yusnika; Yani, Eka Putri (FKIP Universitas Al Washliyah Medan, 2024)
This article is a literature review which aims to provide a study of learning strategies that can be used to improve students' mathematical literacy skills in Indonesia which are still low. In this article, we discuss the factors that cause low mathematical literacy, such as personal factors, instructional factors, and environmental factors and indicators that are used as a reference for the level of mathematical literacy abilities possessed by students. This article also discusses the strategies that have been used by researchers in the research they conducted and stated that they were successful in improving students' mathematical literacy skills with the strategies and use of the learning models they used. So it can be concluded that students' low mathematical literacy skills can be overcome and improved through the use of learning strategies such as learning strategies using the Problem Based Instruction model, learning strategies using the Problem Based Learning (PBL) model and the SQ4R Strategy as well as other strategies that are appropriate and appropriate to the environment. learning around.